Innate and adaptive immune responses to fungi in the airway - Bartemes, Kathleen R.; Kita, Hirohito (Journal of allergy and clinical immunology, 2018)
Fungi are ubiquitous outdoors and indoors. Exposure, sensitization, or both to fungi are strongly associated with development of asthma and allergic airway diseases. Furthermore, global climate change will likely increase the prevalence of fungi and enhance their antigenicity. Major progress has been made during the past several years regarding our understanding of antifungal immunity. Fungi contain cell-wall molecules, such as β-glucan and chitin, and secrete biologically active proteases and glycosidases. Airway epithelial cells and innate immune cells, such as dendritic cells, are equipped with cell-surface molecules that react to these fungal products, resulting in production of cytokines and proinflammatory mediators. As a result, the adaptive arm of antifungal immunity, including TH1-, TH2-, and TH17-type CD4+ T cells, is established, reinforcing protection against fungal infection and causing detrimental immunopathology in certain subjects. We are only in the beginning stages of understanding the complex biology of fungi and detailed mechanisms of how they activate the immune response that can protect against or drive diseases in human subjects. Here we describe our current understanding with an emphasis on airway allergic immune responses. The gaps in our knowledge and desirable future directions are also discussed.